Paging through history: Parchment as a reservoir of ancient DNA for next generation sequencing - BRADLEY, DANIEL (My University, 2015)
Parchment represents an invaluable cultural reservoir. Retrieving an additional layer of information from these abundant, dated livestock-skins via the use of ancient DNA (aDNA) sequencing has been mooted by a number of researchers. However, prior PCR-based work has indicated that this may be challenged by cross-individual and cross-species contamination, perhaps from the bulk parchment preparation process. Here we apply next generation sequencing to two parchments of seventeenth and eighteenth century northern English provenance. Following alignment to the published sheep, goat, cow and human genomes, it is clear that the only genome displaying substantial unique homology is sheep and this species identification is confirmed by collagen peptide mass spectrometry. Only 4% of sequence reads align preferentially to a different species indicating low contamination across species. Moreover, mitochondrial DNA sequences suggest an upper bound of contamination at 5%. Over 45% of reads aligned to the sheep genome, and even this limited sequencing exercise yield 9 and 7% of each sampled sheep genome post filtering, allowing the mapping of genetic affinity to modern British sheep breeds. We conclude that parchment represents an excellent substrate for genomic analyses of historical livestock.
PUBLISHED
Keywords: Parchment; Parchment